Preservice teachers' pedagogical competence and transformation learning in a dual online-offline teaching practicum - Miftah, M. Zaini; Widiati, Utami; Wulyani, Anik Nunuk; Suzila, Tengku Intan (Jurnal Cakrawala Pendidikan, 2024)
The amount of research discussing preservice teachers' (PSTs) critical reflection on teaching practicum in transformative learning (TL) within teacher education programs is evident. However, research investigating PSTs' pedagogical competence (PC) and TL through the lens of critical reflection on Indonesian EFL teaching practicum settings is limited. The study aimed to investigate what PSTs learned from critical reflection on a dual online-offline teaching practicum for developing PC and how they performed TL. Ten PSTs engaged in a two-month teaching practicum experience within the English teacher education preparation program of a state university in Central Kalimantan Indonesia were purposely sampled in this case study. Multiple data were garnered through reflective journals and focus group interviews. Data were analyzed deductively and thematically to explore prominent themes. The results shed some light on lessons learned encompassing the instructional practices for PSTs' PC development and their improved PC. PSTs performed TL by boosting students' ability in changing mindsets and thinking habits in learning and making them aware of learning and becoming better learners. The research implication provides empirical evidence pertaining to how critical reflection on the dual online-offline teaching practicum contributes to PSTs' PC development and TL performance for professional development.